Estudo comparativo entre diversas composições com pisos flutuantes de madeira natural - assoalho e tacos - quanto ao isolamento do ruído de impacto - Neubauer, Paola Mezzomo (2009)
The proposal of this project is analyze and compare different behaviors of natural floating wood floors, submitted an impact noise with several compositions, used in construction industry. The tests were done on the Thermo-acoustic Laboratory of UFSM, in according with the methods specified in the regulations ISO 140/ VI and ISO 717-2. The tests were done, using layers of wood, in different compositions and resilient materials. The results were analyzed, confronting the material with same characteristics but with different composition. The resilient materials used in the tests were: glass wool, polyethylene and polystyrene. The analysis of the results was done grouping the similar materials with different compositions.